The Role of Young Entrepreneurs in Encouraging the Indonesian Economy to Improve National Development - Siska Junianti Br Perangin-angin; Zuhrinal M. Nawawi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
The emergence of young entrepreneurs and the involvement of the active role of entrepreneurs are alternative solutions to the problem of unemployment. Young entrepreneurs have functional roles and strategic positions in accelerating national development. The purpose of this paper is to provide an overview, analysis and discussion of the role of young entrepreneurs in the Indonesian economy and development. The approach used in this paper by using the perspective of national interest and the method used in this paper is a qualitative analysis method. In the role of young entrepreneurs, there are at least three main things that are important discussions, namely important discussions, namely the government's steps to encourage the active role of young entrepreneurs through efforts to create new young entrepreneurs and maximize the role of young entrepreneurs. The second is efforts to develop and empower young entrepreneurs, including contributions and partnerships with organizations and local governments. And the third is regarding the active role of young entrepreneurs in increasing national economic development. Easy entrepreneurs act as innovators whose duties and activities play a role in finding and carrying out reform tasks, planning in formulating business operating guidelines and playing a role in facing challenges risks, as leaders who have a vision of development goals. , as a systematic and strategic decision making in facing the challenges of change as well as acting as a liaison that establishes harmonious, collaborative relations, both internally and externally in an effort to contribute to national development.